Positive Nostalgia and a Feminist Perspective: the Spanish Second Republic as a Roadmap in "Tres tiempos y la esperanza" - Patrick Thompson, John (Madrygal. Revista de Estudios Gallegos, 2017)
This article analyzes two essential components of María Victoria Valenzuela’s autobiographical novel entitled Tres tiempos y la esperanza (1962), which narrates the author’s experiences during the Spanish Second Republic, the Civil War, and the Franco dictatorship. I focus on the role played by nostalgia which, in the first part of the narrative, colors the descriptions of individual memories, as well as the narrator’s comments on the milestones of the Republican period. Nostalgia is usually associated with essentialism and the irrational, but in this novel it can inspire in the reader empathy toward those who defended democracy. I then examine the narrative’s feminist perspective that, on the one hand, highlights fascist violence against women. On the other, it rejects any form of essentialism that endorses the existence of innate differences between men and women. Any distinctions between the sexes are portrayed as consequences of socialization. I uphold this novel, almost completely forgotten by the critics, because of its testimonial value and its ethical and political content. Contrary to many novels that trivialize the past and use the Spanish Civil War as a backdrop, this text’s commemorative task recreates a history free of the fascist fallacies, which continue to underpin the hegemonic version of the events.
Keywords: Trauma; Narrative Fiction; the Spanish Civil War; the Spanish Second Republic; Historical Memory; Francoism.